The Effects of Transcranial Direct Current Stimulation During Extended Reality Exercises for Cortical, Neuromuscular, and Clinical Recovery of Stroke Survivors - Cassio V. Ruas; Bruna M. Carlos; Saulo Feitosa; Márcio Vinícius Silva; Pedro Vazquez; Larissa L. Pontes; Jayne Silvestre; Sara R. M. Almeida; Alexandre F. Brandão; Gabriela Castellano (Neural Plasticity, 2025)
Conclusion: It seems that the application of active atDCS targeted the ipsilesional M1 representation of the quadriceps, which potentiated muscle activation in the paretic rectus femoris during XR exercises and resulted in greater motor recovery in hip flexion movements. The EEG-derived BSI results also indicate that atDCS was effective in reorganizing the ipsilesional hemisphere brain activity after stroke.